A case of hemorrhagic shock in a patient with neurofibromatosis type 1. Issue 2 (27th February 2023) - Sakaguchi, Yutaro; Okano, Hiromu; Furuya, Ryosuke; Otsuka, Tsuyoshi; Miyazaki, Hiroshi
Abstract: Complications of neurofibromatosis type 1 include fatal bleeding events due to vascular fragility. In this case of hemorrhagic shock due to a neurofibroma, the bleeding was controlled using an occlusion balloon and endovascular treatment which stabilized the patient. Systemic vascular investigation for bleeding sites is important to prevent fatal outcomes. Abstract : Complications of neurofibromatosis type 1 include fatal bleeding events due to vascular fragility. In this case of hemorrhagic shock due to a neurofibroma, the bleeding was controlled using an occlusion balloon and endovascular treatment which stabilized the patient. Systemic vascular investigation for bleeding sites is important to prevent fatal outcomes.